KONTRIBUSI PERILAKU DISRUPTIF TERHADAP EKSKLUSI SOSIAL PADA ANAK USIA SD - Amin Lestari; Bambang Sumardjoko; Anatri Desstya; Laili Etika Rahmawati; Endang Fauziati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article identifies the causes of disruptive behaviour (PD) in elementary school children and explains how PD can contribute to social exclusion. The study in this article employs a case study design and is conducted in an elementary school in Sragen Indonesia. Data were gathered through in-depth interviews, participatory observation, and documentation. To test the validity, the researcher used triangulation. The data obtained and declared valid were then analyzed by following the procedures proposed by Miles et al. (2014). They are data condensation, data display, and conclusion drawing or verification. The results showed that (a) the family environment, school environment, playmate environment, and community environment were the determinants of the emergence of children’s disruptive behaviour, (b) the process of social exclusion as a result of PD was applied by following three stages; group assessment of the risk of PD, decision making to exclude perpetrators, and selflimitation of excluded students within a specified time. It could be concluded that based on the four environments that affected children’s disruptive behaviour, the family environment and school environment were frequently determinants. Nevertheless, in some cases, the existence of a role model in the community reinforced the children’s disruptive behaviour. The social exclusion that came from disruptive behaviour (in the third phase) would only be stopped when the perpetrator no longer shows their disruptive behaviour. The researcher recommended to do an early diagnosis of PD symptoms. It is